CD8-positive lymphocyte infiltration as a marker of anti-tumor immune response in rectal cancer: pre- and post-neoadjuvant radiotherapy comparison - Samaneh Salarvand; Romina Abyaneh; Abdorreza Raee; Mahdieh Yaghooti-Khorasani; Fariba Mohammadjani; Fatemeh Nili; Mahdi Aghili; Reza Ghalehtaki (Clinical and Translational Radiation Oncology)
Background: Antitumor immunity, exerted by CD8+ cytotoxic T lymphocytes, plays a vital role in tumor control. Therefore, the present study was conducted to compare the amount of CD8+ tumor-infiltrating lymphocytes (TILs) before and after either long- (LCRT) or short-course radiotherapy (SCRT) in rectal cancer. Methods: This study retrospectively assessed rectal cancer patients treated by neoadjuvant radiotherapy between 2019 and 2021. Biopsy and surgical samples were subjected to immunohistochemical staining to count CD8+ TILs. The association between the post-to-pre-treatment CD8+ count ratio and treatment groups, histopathological factors, and response to treatment was assessed. Results: A total of 34 patients were included, with 23 (67.6 %) receiving LCRT and 11 (32.4 %) receiving SCRT. The mean age was 58.56 ± 13.59 years. The number and percentage of CD8+ TILs increased significantly after radiotherapy in all patients (P < 0.001). An increase in CD8+ TILs was observed in both groups, with LCRT showing a median post-to-pre-treatment count ratio of 2.77 and SCRT showing 3.1 (P = 0.127). A generalized linear multivariate model adjusting for mucinous histology, surgical grade, and pathological stages revealed that SCRT was associated with a significantly higher post-to-pre-treatment CD8+ count ratio compared to LCRT (P = 0.03). Conclusion: Our study highlights that both SCRT and LCRT significantly increase CD8+ TIL count and percentage, reflecting robust immune activation after radiotherapy in rectal cancer, with SCRT showing a higher relative increase, though not statistically significant in unadjusted analyses. After adjusting for histopathological variables, SCRT was independently associated with a greater increase in CD8+ T cells.